2007
DOI: 10.1111/j.1439-0426.2007.00886.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of harvest and length limits on shovelnose sturgeon in the upper Wabash River, Indiana

Abstract: Shovelnose sturgeon Scaphirhynchus platorynchus are one of the few sturgeon species that currently support sustainable commercial harvest. However, harvest closures for many Eurasian sturgeons have resulted in increased exploitation of this fishery, thereby raising concerns about the sustainability of shovelnose sturgeon resources. As a result, the maintenance of self-sustaining shovelnose sturgeon populations will require the estimation of appropriate harvest levels. This study used an age-structured populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 18 publications
5
22
0
Order By: Relevance
“…Population viability was most strongly influenced by changes in the age at which females reach maturity, in the mean fecundity, egg to age 1 natural mortality and juvenile mortality (age groups 1-4), as well as by sex ratio, spawning frequency and adult mortality. These results are in accordance with PVAs performed on North American sturgeon species (Pine et al 2001;Beamesderfer et al 2007;Kennedy and Sutton 2007), that have found that the most influential parameters were egg mortality, age at maturity of females, spawning frequency and the overall natural mortality. Kennedy and Sutton (2007) estimated that the egg mortality was the single most influential population parameter, and an increase of 0.0001% units in mortality rate (from 0.9998 as the average value) caused as much as a 95% decline in population abundance and biomass.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Population viability was most strongly influenced by changes in the age at which females reach maturity, in the mean fecundity, egg to age 1 natural mortality and juvenile mortality (age groups 1-4), as well as by sex ratio, spawning frequency and adult mortality. These results are in accordance with PVAs performed on North American sturgeon species (Pine et al 2001;Beamesderfer et al 2007;Kennedy and Sutton 2007), that have found that the most influential parameters were egg mortality, age at maturity of females, spawning frequency and the overall natural mortality. Kennedy and Sutton (2007) estimated that the egg mortality was the single most influential population parameter, and an increase of 0.0001% units in mortality rate (from 0.9998 as the average value) caused as much as a 95% decline in population abundance and biomass.…”
Section: Discussionsupporting
confidence: 94%
“…These results are in accordance with PVAs performed on North American sturgeon species (Pine et al 2001;Beamesderfer et al 2007;Kennedy and Sutton 2007), that have found that the most influential parameters were egg mortality, age at maturity of females, spawning frequency and the overall natural mortality. Kennedy and Sutton (2007) estimated that the egg mortality was the single most influential population parameter, and an increase of 0.0001% units in mortality rate (from 0.9998 as the average value) caused as much as a 95% decline in population abundance and biomass. Bajer and Wildhaber (2007) have found that the egg, juvenile and young adult mortality were the most influential parameters on the population growth rate, while the fecundity was a less sensitive parameter.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…One study modeled the effects of harvest on shovelnose sturgeon in the upper Wabash River (US) where shovelnose sturgeon are not protected by the SOA provision. They found harvest rates of female shovelnose as low as 15 % negatively affected abundance, yield, and reproductive potential (Kennedy and Sutton 2007). It is unlikely that fisheries for shovelnose sturgeon in the unprotected areas will meet demand in a sustainable manner without very strict regulations by state agencies bordering the rivers, which do not yet exist.…”
Section: A Potential Species-loss Domino-effectmentioning
confidence: 98%
“…For example, there is no commercial harvest in the upper Wabash River (Fig. 3) and this region is known to provide important spawning grounds for shovelnose sturgeon (Kennedy and Sutton 2007). States could consider river reaches of similar importance for reserve establishment.…”
Section: Recommendationsmentioning
confidence: 99%